Dampak pola asuh dan usia penyapihan terhadap status gizi balita indeks BB/U - Masyudi, Masyudi; Mulyana, Mulyana; Rafsanjani, T. M (AcTion: Aceh Nutrition Journal, 2019)
Nutritional status with WFA provides an description of acute nutritional problems, due to fluctuating changes in body weight. Breastfeeding is not until two years is a factor causing weight not to rise, so weaning toddlers very well even at 2 years. Mothers with poor parenting such as breastfeeding, complementary feeding and health services also affect the condition of the nutritional status of children under five acutely. The aim of study was to determine the impact of parenting and weaning age on the nutritional status of toddler. The research was cross-sectional study design, with 65 toddlers in Muara Batu District, North Aceh Regency. Samples are taken randomly. Parenting and weaning data were collected through interviews, while nutritional status data used a WFA z-score index. Analysis using Chi-square test. The results show the relationship between parenting (p= 0,021; OR= 3,6) and weaning age (p= 0,042; OR= 3,5) with the nutritional status of toddlers. In conclusion, poor parenting and the fast age of weaning have an impact on the high number of cases of malnutrition in children under five in Muara Batu District, North Aceh. Suggestions, it is necessary to support health promotion such as counseling related to parenting and weaning, and it is hoped that positive follow-up by relevant stakeholders in improving the nutritional status of toddlers.Status gizi BB/U memberikan gambaran masalah gizi akut, karena perubahan berat badan yang fluktuatif. Pemberian ASI tidak sampai dua tahun merupakan faktor penyebab berat badan tidak naik, sehingga menyapih balita sangat baik genap pada 2 tahun. Ibu dengan pola asuh tidak baik seperti pemberian ASI, MP-ASI dan pelayanan kesehatan berdampak juga terhadap kondisi status gizi balita secara akut. Tujuan penelitian untuk mengetahui dampak pola asuh dan usia penyapihan terhadap status gizi balita. Penelitian berdesain Cross-sectional study, pada balita sebanyak 65 balita di KecamatanÂ Â  Muara Batu, Kabupaten Aceh Utara. Sampel diambil secara acak. Data pola asuh dan penyapihan dikumpulkan melalui wawancara, sedangkan data status gizi menggunakan z-score indeks BB/U. Analisis menggunakan uji Chi-square. Hasil menunjukkan hubungan antara pola asuh (p= 0,021; OR= 3,6) dan usia penyapihan (p= 0,042; OR= 3,5) dengan status gizi balita. Kesimpulan, pola asuh yang kurang baik serta cepatnya usia penyapihan berdampak terhadap tingginya kasus gizi kurang pada balita di Kecamatan Muara Batu, Aceh Utara. Saran, perlu dukungan promosi kesehatan seperti penyuluhan terkait pola asuh pada balita dan penyapihan, serta diharapkan tindak lanjut positif oleh stakeholder terkait dalam meningkatkan status gizi balita.